Achievements and Lessons Learned From Successful Small Satellite Missions for Space Weather‐Oriented Research - Harlan E. Spence; Amir Caspi; Hasan Bahcivan; Jesus Nieves‐Chinchilla; Geoff Crowley; James Cutler; Chad Fish; David Jackson; Therese Moretto Jorgensen; David Klumpar; Xinlin Li; James P. Mason; et al. (Space Weather)
Abstract When the first CubeSats were launched nearly two decades ago, few people believed that the miniature satellites would likely prove to be a useful scientific tool. Skeptics abounded. However, the last decade has seen the highly successful implementation of space missions that make creative and innovative use of fast‐advancing CubeSat and small satellite technology to carry out important science experiments and missions. Several projects now have used CubeSats to obtain first‐of‐their‐kind observations and findings that have formed the basis for high‐profile engineering and science publications, thereby establishing without doubt the scientific value and broad utility of CubeSats. In this paper, we describe recent achievements and lessons learned from a representative selection of successful CubeSat missions with a space weather focus. We conclude that these missions were successful in part because their limited resources promoted not only mission focus but also appropriate risk‐taking for comparatively high science return. Quantitative analysis of refereed publications from these CubeSat missions and several larger missions reveals that mission outcome metrics compare favorably when publication number is normalized by mission cost or if expressed as a weighted net scientific impact of all mission publications.